2017
DOI: 10.3390/nu9060563
|View full text |Cite
|
Sign up to set email alerts
|

A Polish Study on the Influence of Food Neophobia in Children (10–12 Years Old) on the Intake of Vegetables and Fruits

Abstract: Adhering to the recommended intake of fruits and vegetables is an important habit that should be inculcated in children, whereas food neophobia is indicated as one of the most important factors creating food preferences that may interfere. The aim of the presented study was to analyze the association between the food neophobia level and the intake of fruits and vegetables in children aged 10–12 years. The study was conducted among a group of 163 children (78 girls and 85 boys). The assessment of the food neoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 42 publications
5
36
3
Order By: Relevance
“…The additional elements included the assessment of the interfering factors influencing the observed associations. Food neophobia was indicated as one of the potential interfering factors; this was based on a previous Polish study conducted in Warsaw [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The additional elements included the assessment of the interfering factors influencing the observed associations. Food neophobia was indicated as one of the potential interfering factors; this was based on a previous Polish study conducted in Warsaw [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each participant was asked to rate his/her level of agreement with each of the ten sentences, using one of the seven categories of answer (a scale from strongly disagree to strongly agree). For the five “negative item” questions, the scale was reversed during the analysis of data, as is commonly conducted [ 21 , 23 ]. In the present group, Cronbach’s alpha was at a respectable level (0.77; n = 1014), which indicated good internal consistency [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, especially for school children obtaining the recommended intake of fruit and vegetables may be straitened, as their common reluctance or avoidance of unknown food products causes that they often limit the fruit and vegetables intake [7,8]. It corresponds the inadequate fruit and vegetables intake that is commonly observed in various populations of children, including Polish one [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the other studies (Cooke et al, 2003;Tan & Holub., 2012) any associations between children's gender with their FN scores was not observed; however, in a study among children aged 6-9 years, boys showed more neophobic behavior than girls (Guzek et al, 2017).…”
Section: Effect Of Demographics Variables On Food Neophobia Scoresmentioning
confidence: 91%